Safety of cassava and cassava-based products: a systematic review - Forkum, Ambang Tatianne; Wung, Alang Ernest; Kelese, Mark Tata; Ndum, Che Myra; Lontum, Alvin; Kamga, Emmanuel Berinyuy; Nsaikila, Melaine Nyuyfoni; Okwen, Patrick Mbah (Frontiers in Sustainable Food Systems, 2025)
ObjectiveTo establish the current body of evidence regarding the safety of cassava and cassava-based products for human consumption and to identify the most effective preparation methods to reduce toxicity.MethodsThe main databases searched were CABI, PubMed, CINAHL, EMBASE, the Cochrane Database of Systematic Reviews, and the JBI Evidence Synthesis, Science Direct, Agricola, AGRIS, Web of Science, Scopus and Proquest. We limited our search to studies published from 1980 to date. Two independent reviewers were used to review identified titles and abstracts for data extraction that was pooled in a statistical meta-analysis for analyses. We reviewed full papers of relevant abstracts. This data was collected from multiple studies examining hydrogen cyanide (HCN) levels in traditionally soaked cassava chips, cassava biscuits, gari, cassava flour, cassava roots, and cassava paste/dough. HCN content was measured and compared across these products, with results expressed in mg/kg. HCN values in these products were presented on graphs, and mean scores were calculated and compared against FAO/WHO’s maximum recommended dosage of 10 mg/kg.ResultsThe study found significant variations in HCN content across cassava and different cassava-based products and by regions. The recommended FAO/WHO standard is 10 mg/kg, and that the high variation in the samples was due largely to the method of processing the product. Traditionally soaked cassava chips exhibited the highest average HCN levels (46.6 mg/kg). Cassava biscuits showed lower HCN levels, averaging 12 mg/kg. Gari products had an average HCN content of 5.7 mg/kg, while cassava flour exhibited significant variation, with an average of 71.1 mg/kg. Cassava roots and paste/dough also showed high HCN levels, with averages of 60.98 mg/kg and 38.1 mg/kg, respectively. Gari, which is the most popular form of cassava based products is rich in roughage and has a safe level cyanide, and is a potential product for international markets.ConclusionThe findings highlight the potentials of cassava based products for international markets and the critical need for improved cassava processing techniques to reduce HCN levels and mitigate the risk of cyanide poisoning. Effective methods such as fermentation, drying, and combining cassava with other ingredients can significantly lower HCN content. Standardized processing practices, regulatory standards, and community education are essential to ensure the safety of cassava-based products.